INFLUENCE OF HEATING FACTORS ON FORMING OF CARBIDE GRID IN STEEL SHH15SG - A. B. Steblov; V. I. Timoshpolskij; D. V. Lenartovich; S. V. Gunenkova; I. V. Kotov (Литьë и металлургия, 2005)
The manufacturing data on forming of carbide grid in uninterruptedly-casted ingots of bearing steel ShHlSSG depending on technological parameters in preheating and heating furnaces of RUP ‘‘BMZ” are given.